2000
DOI: 10.1515/jpm.2000.012
|View full text |Cite
|
Sign up to set email alerts
|

Soluble intercellular adhesion molecule and C-reactive protein as early markers of infection in newborns

Abstract: In order to find a reliable early marker of infection in newborns a study with simultaneous determination of soluble Intercellular Adhesion Molecule-1 (sICAM-1) and C-Reactive Protein (CRP) was planned. Prospectively 90 babies < 5 days of age suspect of infection were included. Retrospectively this population was classified into an "infected" group (n = 45) and a "non-infected" group (n = 45). For each of these two groups we calculated the sensitivity, specificity and predictive values of sICAM-1 and CRP as ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…sICAM-1 rose in the peripheral blood of both asphyxiated and infected neonates on the 3rd and 5th postnatal days. Several investigators have found increased sICAM-1 serum levels in septicemic newborns (23,24,(34)(35)(36). To the authors' knowledge, measurements of sICAM-1 in neonatal peripheral blood following perinatal asphyxia have not been reported.…”
Section: Discussionmentioning
confidence: 82%
“…sICAM-1 rose in the peripheral blood of both asphyxiated and infected neonates on the 3rd and 5th postnatal days. Several investigators have found increased sICAM-1 serum levels in septicemic newborns (23,24,(34)(35)(36). To the authors' knowledge, measurements of sICAM-1 in neonatal peripheral blood following perinatal asphyxia have not been reported.…”
Section: Discussionmentioning
confidence: 82%
“…12 The results show distinctly different patterns of expression of sICAM-1 between premature and fullterm neonates as a function of septic process. Concentrations of sICAM-1 are very high in neonates with sepsis regardless of their gestational age.…”
Section: Discussionmentioning
confidence: 85%
“…Total NOS scores range from 0 (lowest) to 9 (highest). According to the NOS scores, the included studies were classified into two levels: low quality (0-6), and high quality (7)(8)(9). Discrepancies in the NOS scores of the included articles were resolved by an additional reviewer through discussion and consultation.…”
Section: Methodsmentioning
confidence: 99%
“…Large quantities of bacteria and viruses may to be associated with infant pneumonia, with viral neonatal pneumonias including intrauterine, early-onset or late-onset pneumonias (6). It has been suggested that C-reactive protein (CRP) may be one of the best single tests for the early detection of pneumonia in children, and could be widely used as marker of infection (8).…”
Section: Introductionmentioning
confidence: 99%